Comparing health-related quality of life of employed women and housewives: a cross sectional study from southeast Iran - Saravi Fatihe Kerman; Navidian Ali; Rigi Shahindokht; Montazeri Ali (BMC, 2012)
Abstract Background Quality of life differs for different people in different situations and is related to one's self-satisfaction with life. Considering the role of women in family and social health and the specific cultural characteristics of our province, we aimed to compare the quality of life of employed women with housewives in Zahedan, Iran. Methods This cross-sectional study was carried out during 2009-2010 in Zahedan, Iran. The sample consisted of 110 housewives and 110 employed women selected randomly from ten health care centers. Health-related quality of life was assessed using the SF-36. Analysis of covariance (ANCOVA) was used to compare quality of life in housewives and employed women while controlling for age, education and income. Results The mean (±SD) age of participants was 33.87± 8.95 years. Eighty-eight women (40%) had a university degree with a mean (±SD) official education of 10.8 (±4.9) years. The results indicated that employed women scored higher than housewives in all measures except for physical functioning. The differences were found to be remarkable for vitality, mental health and role emotional. However, after controlling for age, education and family income, none of differences reached significant level. Conclusion After controlling for potential confounders, the findings from this study indicated that there were no significant differences in quality of life between employed women and housewives. However, employed women scored higher on the SF-36, especially on the role emotional, vitality, and mental health. The findings suggest that associations exist between some aspects of health-related quality of life and employment. Indeed improving health-related quality of life among housewives seems essential.